[POSTER] RGB-D/C-arm calibration and application in medical augmented reality - Wang, Xiang; Habert, Severine; Ma, Meng; Huang, Chun-Hao; Fallavollita, Pascal; Navab, Nassir (Proceedings of the 2015 IEEE International Symposium on Mixed and Augmented Reality, ISMAR 2015, 2015)
Calibration and registration are the first steps for augmented reality and mixed reality applications. In the medical field, the calibration between an RGB-D camera and a mobile C-arm fluoroscope is a new topic which introduces challenges. In this paper, we propose a precise 3D/2D calibration method to achieve a video augmented fluoroscope. With the design of a suitable calibration phantom for RGB-D/C-arm calibration, we calculate the projection matrix from the depth camera coordinates to the X-ray image. Through a comparison experiment by combining different steps leading to the calibration, we evaluate the effect of every step of our calibration process. Results demonstrated that we obtain a calibration RMS error of 0.54±1.40 mm which is promising for surgical applications. We conclude this paper by showcasing two clinical applications. One is a markerless registration application, the other is an RGB-D camera augmented mobile C-arm visualization.
CRIS-Team Scopus Importer:2023-03-08